2014
DOI: 10.1093/glycob/cwu025
|View full text |Cite
|
Sign up to set email alerts
|

A Burkholderia cenocepacia MurJ (MviN) homolog is essential for cell wall peptidoglycan synthesis and bacterial viability

Abstract: The cell wall peptidoglycan (PG) of Burkholderia cenocepacia, an opportunistic pathogen, has not yet been characterized. However, the B. cenocepacia genome contains homologs of genes encoding PG biosynthetic functions in other bacteria. PG biosynthesis involves the formation of the undecaprenyl-pyrophosphate-linked N-acetyl glucosamine-N-acetyl muramic acid-pentapeptide, known as lipid II, which is built on the cytosolic face of the cell membrane. Lipid II is then translocated across the membrane and its glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…A less commonly used but tightly controlled inducible promoter system is the rhamnose-inducible E. coli rhaSR-PrhaBAD (26,27). Although Valvano and coworkers showed that the E. coli rhaSR-PrhaBAD system is tightly controlled in Burkholderia cenocepacia (28) and used it to identify and study essential genes (29)(30)(31)(32), the functionality of this system in P. aeruginosa has not been reported. We constructed and tested two alternative inducible promoter systems for use in P. aeruginosa, miniTn7-lacI q -Ptac and miniTn7-rhaSR-PrhaBAD.…”
Section: Resultsmentioning
confidence: 99%
“…A less commonly used but tightly controlled inducible promoter system is the rhamnose-inducible E. coli rhaSR-PrhaBAD (26,27). Although Valvano and coworkers showed that the E. coli rhaSR-PrhaBAD system is tightly controlled in Burkholderia cenocepacia (28) and used it to identify and study essential genes (29)(30)(31)(32), the functionality of this system in P. aeruginosa has not been reported. We constructed and tested two alternative inducible promoter systems for use in P. aeruginosa, miniTn7-lacI q -Ptac and miniTn7-rhaSR-PrhaBAD.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, if the undecaprenyl moiety of lipid II stays in the hydrophobic core of the membrane during flipping, the flippase would have to have an open slot between two TMDs. The structural models of MurJ from E. coli (14) and B. cenocepacia (12) and of YtgP predict two of these features that are conserved in all three proteins. These open slots are present between TMDs 1 and 8 and TMDs 1 and 5 (see Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The IM protein MurJ is essential for PG biogenesis and functions as the lipid II flippase (9)(10)(11). In agreement with this function, (i) MurJ depletion leads to the accumulation of PG precursors and cell lysis (10)(11)(12); (ii) MurJ belongs to the MVF family of the multidrug/oligosaccharidyl-lipid/polysaccharide (MOP) exporter superfamily, which includes other flippases (13); (iii) MurJ contains a central hydrophilic cavity within the hydrophobic core of the membrane (14); (iv) residues within this hydrophilic cavity are essential for MurJ function (14); and (v) chemical inactivation of MurJ function rapidly stops lipid II flipping and leads to the accumulation of lipid II at the inner leaflet of the IM (9). Although we do not understand how MurJ functions in lipid II translocation, it likely shares functional features with members of the MOP exporter superfamily.…”
mentioning
confidence: 89%
See 2 more Smart Citations